Pengembangan Sistem Penyediaan Air Minum Berbasis Masyarakat di Kabupaten Jember (Studi Kasus Kecamatan Ledokombo) - Arif Hidayatulloh (Fakultas Teknik, 2024)
The Indonesian government has a target of 100% access to safe drinking water by 2030, including Jember Regency, especially in the Ledokombo District area. Ledokombo District has 10 villages, but there are some areas that are not yet served by an optimal pipe network. Apart from the drinking water network service which is not yet optimal, the problem with drinking water for residents in Ledokombo is the low water discharge from the residents' wells during the dry season. This situation provides potential for the development of PAMSIMAS so that it can provide drinking water services and overcome community drinking water problems, especially in Ledokombo District. The aim of this research is to create a Detailed Engineering Design (DED) to support the needs for developing drinking water supplies in Sumber Bulus Village, Sumber Lesung Village and Ledokombo Village. Hydraulic analysis through 2 scenarios of the PAMSIMAS Sumber Bulus pipeline network using EPANET 2.2, along with creating a PAMSIMAS pipeline network design using QGIS. The development of the drinking water supply system is planned for 15 years, from 2023 to 2038. The results of the analysis shows that the average water demand for PAMSIMAS Sumber Bulus users in the projected year 2038 is 13.361 liters/second. The PAMSIMAS Sumber Bulus distribution pipe network in Ledokombo District serves 3 villages, namely Sumber Bulus Village, Sumber Lesung Village, and Ledokombo Village with a total of 2174 house connections. The total cost required for the development of PAMSIMAS in Ledokombo District, Jember Regency until 2038 is approximately IDR 2,688,955,531.00 (two billion six hundred eight
Entry oleh Arif 2026 Maret 16
Keywords: Drinking water system; EPANET scenario; Ledokombo; PAMSIMA